Extração por ponto nuvem de azul de metileno - Diógenes, Ronald Rafael Urbano (Universidade Federal Rural do Semi-Árido, 2017)
The generation of effluent in the textile industry is inevitable. As a consequence, the environmental impacts are very noticeable and harmful to the environment. An alternative to this problem is the cloud point extraction involving the application of non-ionic surfactant at temperatures above the cloud point, the solution becomes cloudy making the water a weak solvent for the surfactant, providing the agglomeration of these molecules around the Pollutant by affinity to the organic phase. In this study, Methylene Blue (AM) was used as the model pollutant. The objective was to solubilize the AM molecules in the polyethoxylated nonyl phenol surfactant, varying the concentration of surfactant, temperature and addition of sodium chloride to study its effects. Temperatures of 60, 65 and 70ºC were evaluated. The results show that the cloud point extraction is an efficient method, reaching 70.93% removal efficiency for the treatment of AM containing effluent.
Keywords: Ponto de Nuvem; Cloud Point; Corantes; Dyes; Indústria Têxtil; Textile Industry; Tensoativo; Tensiatory; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA